Linkage of Macro- and Microscale Modeling Tools for Additive Manufacturing of Steels - Sjöström, Julia; Durga, A.; Lindwall, Greta (Frontiers in Materials, 2022)
Additive manufacturing (AM) offers several benefits including the capability to produce unique microstructures, geometrical freedom allowing for material and energy savings, and easy production lines with fewer post-processing steps. However, AM processes are complex and phenomena occurring at different length and time scales need to be understood and controlled to avoid challenges with, e.g., defects, residual stresses, distortions and alloy restrictions. To overcome some of these challenges and to have more control over the final product, computational tools for different length scales need to be combined. In this work, an 18Ni300 maraging steel part is studied to understand the link between the process parameters and the as-built microstructure. The temperature evolution during laser powder-bed fusion is simulated using the MSC Simulation Software Simufact Additive. This result is then linked to microscale models within the Thermo-Calc Software Package to predict the elemental micro-segregation, martensite start (Ms) temperature and martensite fraction. Different values of the key process parameters such as laser speed, laser power, heating efficiency and baseplate temperature are considered, leading to different thermal histories. The thermal histories affect the elemental segregation across the solidification structure, which in turn, results in different Ms temperatures at different locations of the built part. It is found that a higher laser energy generally causes higher temperatures and larger cooling rates, which results in larger degree of elemental segregation and lower Ms temperatures in segregated regions. Furthermore, the segregated regions are predicted to have Ms temperatures below 200 ˚C, which would result in retained austenite when using a baseplate temperature of 200 ˚C. On the other hand, by using a baseplate temperature of 100 ˚C, all regions would reach temperatures below the Ms temperature and an almost fully martensitic structure would be achieved. In summary, it is demonstrated how the linkage of macro- and microscale modelling tools for AM can be used to optimise the process and produce the desired microstructure and thereby the mechanical properties.